THE HISTORY OF THE NATIONAL THEATER FORMATION IN THE ASSESSMENT OF L. STARYTSKA-CHERNIAKHIVSKA (ON THE BASIS OF THE MATERIAL OF THE WORK “TWENTY-FIVE YEARS OF UKRAINIAN THEATER (MEMORIES AND THOUGHTS)”) - Вільна, Ярослава (SWorldJournal, 2024)
The article analyzes specific aesthetic, artistic and ideological priorities of the writer L. Starytska-Cherniakhivska. It has been established and proved that in these memoirs, to be still qualified today as historiographical and theater works, the cons